Vocal fold myxoma: a case report and review of current literature - Mohammad Nasir, Zuraini; Mohamed, Mohd Hazmi; Bakrin, Ikmal Hisyam; Loh, Tze Liang (Springer, 2022)
Background: Vocal fold myxoma is a rare mesenchymal tumor with unknown exact etiology. The aim of this report is to review current literature on demographic and clinical features of vocal fold myxomas in order to increase awareness among otorhinolaryngologists on management of this rare vocal fold pathology. Case presentation: We report a case of a 46-year-old female teacher presented with 1 year history of progressive dysphonia with no airway obstructive or constitutional symptoms. Flexible laryngoscopy revealed a polypoid mass at the anterior two thirds of the left vocal fold. We proceeded with endolaryngeal microsurgery, where a left vocal fold mass with prominent overlying blood vessels was incompletely excised due to poor plane, in an attempt to prevent injury to vocal ligament. The histopathological findings were consistent with myxoma. No evidence of recurrence was noted at 2 months postoperatively. Conclusions: Vocal fold myxoma should be considered as a differential diagnosis of vocal fold pathology clinically resembling vocal fold polyp, especially in older male adults. Complete excision with removal of a rim of surrounding tissue is the gold-standard treatment to prevent recurrence. If diagnosis is uncertain, intraoperative frozen section can be performed to ensure margins are free from tumor. Life-long follow-up is recommended in incomplete excision of tumor.